Adiponectin Enhances Quiescence Exit of Murine Hematopoietic Stem Cells and Hematopoietic Recovery Through mTORC1 Potentiation. (23rd May 2017) - Masamoto, Yosuke; Arai, Shunya; Sato, Tomohiko; Kubota, Naoto; Takamoto, Iseki; Kadowaki, Takashi; Kurokawa, Mineo
Abstract : Myelotoxic injury, such as chemotherapeutic agents and ionizing radiation, unlocks the vigorous power of hematopoietic stem cells (HSCs) to replenish the hematopoietic system, making quiescent HSCs enter the cell cycle. Considering that both HSC-intrinsic and -extrinsic mechanisms enforce quiescence of HSCs, the drastic change in bone marrow (BM) environment after injury, represented by massive expansion of BM adipocytes, might trigger HSC activation. BM adipocytes, the major cellular component in the ablated marrow, however, reportedly suppress proliferation of hematopoietic cells, which may indicate the BM adipocytogenesis is an irrational response of injured organism. Given that adipose tissue is an endocrine organ with pleiotropic functions, we hypothesized that adipocyte-derived factors, especially adiponectin, an anti-inflammatory adipokine involved in regulation of granulopoiesis, are implicated in HSC activation. Myeloablative intervention increased BM adiponectin by multiple mechanisms, including adipocyte expansion and increased diffusion from the blood. Adiponectin-null ( Adipoq   −/− ) mice showed delayed hematopoietic recovery after BM injury, with Adipoq −/− HSCs more quiescent and defective in mammalian target of rapamycin complex 1 (mTORC1) activation. Recombinant adiponectin promoted not only HSC activation in vivo but cytokine-induced activation in vitro, and shortened the time for exit from quiescence in an mTORC1-dependent manner. These data illustrate a scarcely-reported example of a cell-extrinsic factor, adiponectin, enhancing quiescence exit of HSCs, and subsequent hematopoietic recovery. Our findings also highlight adipocytes as a source of adiponectin to ensure the proliferative burst of hematopoietic cells in ablated marrow.